2015
DOI: 10.1073/pnas.1508187112
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of antizyme-mediated regulation of polyamine homeostasis

Abstract: Polyamines are organic polycations essential for cell growth and differentiation; their aberrant accumulation is often associated with diseases, including many types of cancer. To maintain polyamine homeostasis, the catalytic activity and protein abundance of ornithine decarboxylase (ODC), the committed enzyme for polyamine biosynthesis, are reciprocally controlled by the regulatory proteins antizyme isoform 1 (Az 1 ) and antizyme inhibitor (AzIN). Az 1 suppresses polyamine production by inhibiting the assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 36 publications
5
91
0
Order By: Relevance
“…Additional EM studies of a much larger and functionally distinct oligomeric form of the eukaryotic Fe-S assembly complex are also consistent with an NFS1 quaternary structure different from IscS (62). Another PLP-containing enzyme, ornithine decarboxylase, also uses quaternary structure differences to modulate activity (63). Overall, we propose that eukaryotes have adopted a cysteine desulfurase architecture that allows FXN and ACP to control Fe-S cluster biosynthesis.…”
Section: Discussionsupporting
confidence: 60%
“…Additional EM studies of a much larger and functionally distinct oligomeric form of the eukaryotic Fe-S assembly complex are also consistent with an NFS1 quaternary structure different from IscS (62). Another PLP-containing enzyme, ornithine decarboxylase, also uses quaternary structure differences to modulate activity (63). Overall, we propose that eukaryotes have adopted a cysteine desulfurase architecture that allows FXN and ACP to control Fe-S cluster biosynthesis.…”
Section: Discussionsupporting
confidence: 60%
“…Antizyme has also been reported to bind to Smad1, cyclin D1 and Aurora-A (288)(289)(290), though there has been some controversy about this. A study of the binding sites of antizyme and cyclin D1 also revealed that binding affinity was 4-fold lower than for antizyme and ornithine decarboxylase (291) for which high resolution structural information is now available (276).…”
Section: Antizyme: Frameshifting As a Sensor And Effector For Polyamimentioning
confidence: 99%
“…Interaction between AZ and ODC greatly stimulates ODC degradation. In contrast, interaction with AZ actually stabilizes AZIN1 by interfering with its ubiquitination . Therefore, it is tempting to hypothesize that, similar to the conformational alteration, AZ imposes on ODC resulting in exposure of the C‐terminal degradation signal.…”
Section: Degradation Of Azin1mentioning
confidence: 99%